ANALISIS SEMIOTIKA PADA SIMBOL UPACARA MANGUPA SEBAGAI TRADISI BATAK TOBA - Innova Riana Yanti Sinambela; Rosmawaty Harahap; Elly Prihasti Wuriyani (JOEL: Journal of Educational and Language Research, 2022)
Mangupa tradition is a hereditary tradition. This study aims to determine the meaning of the symbols in the mangupa ceremony with the main ingredients of arsik carp and complementary materials that have their own meaning. This research is a type of descriptive research with a qualitative approach because it provides a clear explanation of the object, data collection is done by interviewing, recording, and taking notes. The method of data analysis in this study uses the theory of the triangle of meaning Charles Sanders Peirce. The results of this study indicate that five symbols are appointed in the Toba Batak traditional mangupa ceremony, namely arsik carp, aek sitio-tio, pandan mat, ulos, and boras si pir ni tondi.